"Where I become you" - A practical theological reading of Antjie Krog’s concept of interconnectedness - Brouwer, R (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
An exposé on Antjie Krog’s Begging to be Black might be a contribution to this conference on ‘Covert violence and human dignity’. What I present today, is a reading of this book, a practical theological reading. The book itself presents a hermeneutical key to the practices of life, and maybe also the practices of faith. Krog’s hermeneutics is familiar to the four dimensions within a cyclical process of discerning: description, interpretation, normativity, strategy. These hermeneutical dimensions could be found in Begging to be Black, and we might even read them in all of Krog’s prose. I start with how Krog describes reality, followed by how she interprets this reality and how she reflects on the interpretation with a normative edge to it, completed with some practical, strategic suggestions. Krog shows that interconnectedness is the only way to survive violence and to preserve human dignity.